A Different Way to Stay in Touch with ‘Urban Nature’: The Perceived Restorative Qualities of Botanical Gardens - Carrus, Giuseppe; Scopelliti, Massimiliano; Panno, Angelo; Lafortezza, Raffaele; Colangelo, Giuseppe; Pirchio, Sabine; Ferrini, Francesco; Salbitano, Fabio; Agrimi, Mariagrazia; Portoghesi, Luigi; Semenzato, Paolo; Sanesi, Giovanni (Frontiers in Psychology, 2017)
Botanical gardens represent interesting arenas for research in environmental psychology and environment-behavior relations. They can be considered a very particular type of restorative environment and also have a relevant social function for the promotion of a more sustainable lifestyle in current societies. In this paper, we present a study assessing the relationship between the perceived restorativeness, the psychological and physical benefits experienced, and the subjective wellbeing reported by visitors of botanical gardens in four different cities in Italy (N = 127). As expected, a bootstrapping mediation model supported the idea that perceived restorativeness of botanical gardens significantly predicts visitors’ subjective wellbeing, both directly and indirectly through perceived physical and psychological benefits of the visit. A moderation model also revealed that the relationship between restorativeness and wellbeing varies across respondents with different socio-demographic characteristics, being stronger for singles as compared to couples with and without children, respectively. The theoretical and practical implications of these findings are discussed.